Effect of pentobarbital on visual processing in man - Martin, Ernst; Thiel, Thorsten; Joeri, Philipp; Loenneker, Thomas; Ekatodramis, Dimitri; Huisman, Thierry; Hennig, Juergen; Marcar, Valentine L. (Human brain mapping, 2000)
To investigate the effect of sedative agents on visual processing in humans, we analysed the BOLD contrast signal response to a visual stimulation paradigm in 15 healthy, adult volunteers using functional magnetic resonance imaging. The subjects were tested during alert state and under sedation following intravenous administration of pentobarbital. The injection of pentobarbital not only significantly reduced the response signal strength but the reduction in BOLD contrast signal was related to the ratio of amount of sedative administered and the subject's body weight. The three subjects with the highest relative sedative dosage even displayed an inverted (negative) BOLD contrast signal. A significant reduction in the number of positively correlating pixels was found 15 min after administration of pentobarbital. All measured parameters returned to near pre‐sedative levels by the end of the experimental session. The relative dosage dependence of the strength of the BOLD signal the negative BOLD signal in the three subjects with the highest relative sedative dosage indicates that pentobarbital had a more pronounced effect on cerebral blood flow than on cerebral oxidative metabolism. Hum. Brain Mapping 10:132–139, 2000. © 2000 Wiley‐Liss, Inc.